The Relevance of Cultural, Fatalistic and Psychosocial Factors in Breast Cancer Screening Behavior in Middle Age and Older Women - Cermignani, Luciano (2023)
The aim of this study was to analyze cultural and social factors in advantaged and disadvantaged women in relation to mammographic screening. A cross-sectional study was performed; 850 women aged 45-79 years were interviewed; based on socioeconomic aspects, women were grouped in low economic power (Low group, LG) (379 women) and middle economic power (MG) (471). A questionnaire previously validated was employed and information about cultural, fatalistic, and psychosocial factors as well as breast cancer and mammographic screening was assessed. An extensive statistical analysis was performed including three regression models and a principal component analysis. 98% MG and 49.7% LG had a high level of education. Women who stated having a high level of education, regularly visit a doctor and being communicatively open showed the most positive mammographic screening behaviors. In general, analysis of fatalistic affirmatives in relation to mammogram variables did not show a significant difference in relation to total MG and LG while psychosocial variables showed a very low significant relationship with mammographic screening. Regression analysis showed similar results. This study highlights that communication as well as family and social support constitute important factors which impact on mammographic screening, while fatalism, although present, should not constitute a crucial aspect.